Clinical Phenotype in a Toddler with a Novel Heterozygous Mutation of the Vitamin D Receptor - Preneet Cheema Brar; Elena Dingle; John Pappas; Manish Raisingani (Case Reports in Endocrinology)
We present the clinical phenotype of a toddler who presented with vitamin D-resistant rickets, with one of the highest initial levels of alkaline phosphatase and parathyroid hormone (PTH) levels reported in the literature. The toddler had novel compound heterozygous mutations in the ligand-binding site of the vitamin D receptor and had an excellent response to calcitriol (1,25(OH)2D).